Era of Post-Pragmatical Strategies - Reut, Dmitry (Slavica, 2020)
An extended definition of culture as a phenomenon that includes processes and results of human communities interaction with wildlife, e.g. viruses is propounded. An indicator of development limitations of Global civilization-cultural integrity is proposed. We put forward the concept of a post-pragmatic strategy of a cultural unit. The latter signifies social integrity that represents a separate culture – a stable set of traits, categories, patterns reproduced in series of generations. We believe a cultural unit to be a large-scale system. Our study is carried out in the context of the emerging intellectual discipline Hygiene of Culture with the help of methodology of sustainable reproduction of a cultural unit. The aim of the study is to form methodological bases for the reaction of cultural unit aimed at confronting phenomena similar to COVID-19. The result is altruistic post-pragmatic strategy, free of mistrust. We propose to supplement the known security dilemma as follows. Actors allocate their military budgets in proportion to confidence/mistrust rates to opponents while likelihood of risk events in the environment increases according to sandpile model and information noise rises.